Towards lignin-derived chemicals using atom-efficient catalytic routes - Sudarsanam, Putla; Ruijten, Dieter; Liao, Yuhe; Renders, Tom; Koelewijn, Steven-Friso; Sels, Bert F. (Trends in Chemistry, 2020)
Lignin is a potential non-fossil resource of diverse functionalized phenolic units. The most important lignin- derived monomers are 4-alkylphenols, 4- hydroxybenzaldehydes, 4-hydroxybenzoic acids, and 4-hydroxycinnamic acids/esters. Efficient transformation of lignin and/or its monomers into valuable aromatics and their derivatives is crucial, not only for a sustainable lignocellulose biorefinery, but also to reduce our dependence on fossil feedstocks. This review provides a concise account of the recent advances in lignocellulose fractionation/lignin depolymerization processes towards lignin-derived monomers. Subsequently, numerous potential atom-efficient catalytic routes for upgrading lignin monomers into drop-in chemicals and new polymer building blocks are discussed.